RESPON PERTUMBUHAN DAN HASIL MICROGREENS KEMBANG KOL TERHADAP PEMBERIAN AIR KELAPA PADA BERBAGAI MEDIA TANAM: Air Kelapa; Microgreens, Kembang Kol; Media Tanam; Pertumbuhan Tanaman - Husna, Arifah; Ihsan, Mohamad; Pamujiasih, Tri (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
A healthy lifestyle has become increasingly popular in Indonesia, with people becoming more mindful of their eating habits and the ingredients they consume. One of the healthy foods that has gained popularity is microgreens, such as cauliflower microgreens, which have a soft texture and are rich in nutrients. This study aims to examine the effect of coconut water on the growth and yield of cauliflower microgreens in different growing media. The results of the study show that the application of coconut water significantly affects plant height, leaf number, root length, fresh weight, and germination percentage. Cocopeat proved to be the best growing medium for cauliflower microgreens, although no significant interaction was found between coconut water application and growing media in relation to some other growth parameters. This study also suggests further research on the appropriate dosage of coconut water and testing the nutritional content of cauliflower microgreens.